Hong Kong's reunion with China: The global dimension - TANG, James T. H. (Institutional Knowledge at Singapore Management University, 2008)
Hong Kong people are understandably anxious about their future, as the twentieth century ends. This concern follows an old pattern, however; and they may fare as well in this turn as in the past. The “British Crown Colony” ended sometime ago, in popular imagination if not in law. By slow steps and without public fanfare, it was replaced by a more modern, less politically or colorfully described “Territory." In the new “Special Autonomous Region” of China, people wonder whether they can maintain their prosperous growth and diverse lifestyle. They are likely to do so, because Hong Kong has long depended—even in politics—far more on trends inside China than either the colonial government or the city’s people have liked to conceive, and the recent spate of PRC conservatism is not dominant over other Chinese trends. The long term, as revolutionary centralization falls to market coordination in China, bodes very well for Hong Kong’s future.